2022
DOI: 10.35516/jjps.v15i2.320
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cross-Sectional Study- Knowledge, behavior and psychological change among Medical and Non-medical Students in Jordan during COVID-19 pandemic

Abstract: Background: Coronavirus disease 2019 (COVID-19) has rapidly spread worldwide, and it was officially declared to be a pandemic by the World Health Organization on March 11, 2020. COVID-19 is associated with increasing morbidity and mortality and has impacted the lives of the global populations. Aim: To compare the knowledge of medical and non-medical students at Jordanian universities in issues related to COVID-19 and to evaluate the psychological and behavioural changes in Jordanian students’ lives follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The analysis revealed that Pep_D FANCISVTCQCQ is the most promising vaccine candidate against the Nipah virus. Pep_D holds significant potential as an epitopebased peptide vaccine candidate due to its exceptionally low binding energy score, facilitating the formation of molecular complexes [19,20,21,22].…”
Section: Fig 3 Visualization Of the Bond Between The Ligand And The R...mentioning
confidence: 99%
“…The analysis revealed that Pep_D FANCISVTCQCQ is the most promising vaccine candidate against the Nipah virus. Pep_D holds significant potential as an epitopebased peptide vaccine candidate due to its exceptionally low binding energy score, facilitating the formation of molecular complexes [19,20,21,22].…”
Section: Fig 3 Visualization Of the Bond Between The Ligand And The R...mentioning
confidence: 99%
“…Although Jordan is known for its conservative Islamic values, substance use has become increasingly common 12,28,29 . It was reported that tobacco is considered a "gateway drug" that may lead to alcohol, hashish, and other substance use as well high-risk behaviors in the long term in Jordan (Abdel-Qader et al 2021).…”
Section: Substance Use Among Universities Studentsmentioning
confidence: 99%
“…It has been established that the pandemic's impacts extend beyond the psychological effects and high mortality rates of affected individuals. Mental health and lifestyle have also been affected (2) .…”
Section: Introductionmentioning
confidence: 99%